The Effect of Self-Discrepancy on e-WOM and Purchase Intention through Subjective Well-being in Influencer Marketing on Instagram - Grace, Michelle; Purmono, Bintoro Bagus; Afifah, Nur; Setiawan, Harry (Ilomata International Journal of Management, 2025)
This study seeks to investigate the impact of self-discrepancy on consumer behavior in Indonesia regarding influencer marketing on Instagram, employing the mediating role of subjective well-being (SWB)—specifically life satisfaction, positive affect, and negative affect—on e-WOM and purchase intentions. This research uses a quantitative approach, analyzing data from 211 active Instagram users who follow influencers, selected through purposive sampling and analysis tools using Structural Equation Modeling (SEM) with Amos 22. The results reveal that self-discrepancy significantly influences positive affect, negative affect, and life satisfaction. Both positive and negative affect significantly impact e-WOM and purchase intentions, while life satisfaction only affects e-WOM. The study's findings give marketers and influencers fresh perspectives on how to improve their marketing tactics by taking the audience's psychological state into account. This will boost marketing efficacy and favorably affect consumer behavior.